2015
DOI: 10.1002/tox.22155
|View full text |Cite
|
Sign up to set email alerts
|

Study of the chlorpyrifos neurotoxicity using neural differentiation of adipose tissue‐derived stem cells

Abstract: Chlorpyrifos (CPF) is the most commonly used organophosphorus insecticide which causes neurodevelopmental toxicity. So far, animals have been used as ideal models for neurotoxicity studies, but working with animals is very expensive, laborious, and ethically challenging. This has encouraged researchers to seek alternatives. During recent years, several studies have reported successful differentiation of embryonic and adult stem cells to neurons. This has provided an excellent model for neurotoxicologic studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 59 publications
(69 reference statements)
0
12
0
Order By: Relevance
“…BMSCs and ADSCs are known to differentiate into neurons ( 22 , 23 ). In our study, nestin, a neural precursor stem cells marker, and β-tubulin III, an immature neuronal marker, were expressed in native BMSCs and ADSCs, which suggested that both MSCs retained a native potential for neuronal differentiation and were in conformity with other studies ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…BMSCs and ADSCs are known to differentiate into neurons ( 22 , 23 ). In our study, nestin, a neural precursor stem cells marker, and β-tubulin III, an immature neuronal marker, were expressed in native BMSCs and ADSCs, which suggested that both MSCs retained a native potential for neuronal differentiation and were in conformity with other studies ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Neither study quantified the cholinesterase activity. Another study used adipose-derived stem cells to model CPF toxicity [ 43 ] but used a much higher dose of CPF (500 μM), finding decreased viability in differentiating cells. One study examined differentiation outcomes in embryonic stem cell-derived NPCs, finding reduced proportions of glial cells upon exposure to 10–30 μM CPF [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neither study quantified cholinesterase activity. Another study used adiposederived stem cells to model CPF toxicity [44], but used a much higher dose of CPF (500 μM),…”
Section: Discussionmentioning
confidence: 99%
“…Others used neuron-like cell lines including N2a and PC12 cells, identifying cellular effects such as neurite retraction [46,47], which would reflect events much later than the initial NSC differentiation modeled here. Our goal was to identify specific mechanisms affected early in NSC differentiation, since these events are likely to cause changes in differentiation choice, such as the reduced glial differentiation [44], or changes in neuronal circuitry due to shifted differentiation patterns.…”
Section: Discussionmentioning
confidence: 99%